The Validity and Reliability of Turkish Version of the Jenkins Sleep Evaluation Scale in Rheumatoid Arthritis - Mehmet Tuncay DURUÖZ,; Çağrı ÜNAL,; Fırat ULUTATAR,; Canan SANAL TOPRAK,; Osman Hakan GÜNDÜZ, (Archives of Rheumatology, 2018)
Objectives: This study aims to assess the validity and reliability of the Jenkins Sleep Evaluation Scale (JSS) when applied to a Turkish population with rheumatoid arthritis. Patients and methods: The Turkish version of JSS (JSS-TR) was obtained after translation from English into Turkish, according to standard guidelines. The study included 61 patients of rheumatoid arthritis (13 males, 48 females; mean age 50.5 years; range 19 to 72 years) as defined by the American College of Rheumatology 2010 criteria. The internal consistency (Cronbach’s alpha) was assessed for reliability. Content and construct validity (convergent and divergent validities) were evaluated. The relationships between the JSS-TR and the Pittsburgh Sleep Quality Index, the Multidimensional Assessment of Fatigue scale, subgroups of the Nottingham Health Profile, and the Stanford Health Assessment Questionnaire were assessed for convergent validity. In addition, the relationships between the JSS-TR and age, disease duration, visual analog scale patient global score, and disease activity score 28 were assessed for divergent validity. Results: The Cronbach’s alpha of JSS-TR was 0.80. All questions and the answer choices for the scale were understood well and related to some dimension of sleep demonstrating good content validity. The JSS-TR had good correlations with functional parameters (which are convergent), and poor or insignificant correlations with non-functional parameters (which are divergent). This implies that the JSS-TR had good construct validity in the context of this study. Overall, the JSS-TR had the best correlation with the Pittsburgh Sleep Quality Index (Spearman’s rank correlation coefficient=0.76). Conclusion: The JSS-TR is a valid and reliable instrument. It is a simple and effective tool which can be used to evaluate sleep disturbances in rheumatoid arthritis patients in both daily practice and clinical research.